2006
DOI: 10.1348/000712606x114057
|View full text |Cite
|
Sign up to set email alerts
|

Do people with autistic spectrum disorder show normal selection for attention? Evidence from change blindness

Abstract: People in the general population are typically very poor at detecting changes in pictures of complex scenes. The degree of this 'change blindness', however, varies with the content of the scene: when an object is semantically important or contextually inappropriate, people may be more effective at detecting changes. Two experiments investigated change blindness in people with autism, who are known from previous research to be efficient in detecting features yet poor at processing stimuli for meaning and contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 42 publications
12
53
3
Order By: Relevance
“…In the results presented here, no evidence was found of any difference between the capacity of individuals with ASD and IQmatched controls. This is similar to the findings of Fletcher-Watson et al (2006) who demonstrated that the ability to detect changes was equivalent in both ASD and control groups, and may also be consistent with Burack's work (Burack et al, 2009a) that suggests differences will only be seen when developmental level is taken into account. The absence of any increased level of visual short-term memory capacity would suggest that the increased distraction at high perceptual load seen in ASD in experiments one and two is not due to increased capacity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the results presented here, no evidence was found of any difference between the capacity of individuals with ASD and IQmatched controls. This is similar to the findings of Fletcher-Watson et al (2006) who demonstrated that the ability to detect changes was equivalent in both ASD and control groups, and may also be consistent with Burack's work (Burack et al, 2009a) that suggests differences will only be seen when developmental level is taken into account. The absence of any increased level of visual short-term memory capacity would suggest that the increased distraction at high perceptual load seen in ASD in experiments one and two is not due to increased capacity.…”
Section: Discussionsupporting
confidence: 89%
“…When shown videos with continuity errors, the adolescents with autism were significantly better at detecting the errors. A study by Fletcher-Watson et al (Fletcher-Watson et al, 2006), however, failed to show a difference between the ability of control individuals and individuals with ASD to detect changes in visual scenes. Likewise, Burack et al (2009a) also reported no difference in performance on a change detection task.…”
Section: Predictionsmentioning
confidence: 92%
See 1 more Smart Citation
“…This paradigm has been shown to be appropriate for use with highfunctioning individuals with ASD (Fletcher-Watson, Leekam, Turner & Moxon, 2006). Objects in various locations within a scene appeared and disappeared whilst gaze direction of the person in the photo was systematically manipulated between trials.…”
Section: Methodsmentioning
confidence: 99%
“…However, it may not just be the detection of appropriate targets that differs for individuals with autism. Fletcher-Watson, Leekam, Turner and Moxon (2006) suggest that individuals who are high-functioning on the autistic spectrum show a typical attention selection strategy but this is combined with difficulty switching or disengaging attention. In much the same way as evidence proposing attention switching atypicalites in WS (e.g.…”
mentioning
confidence: 99%